Cancer survival disparities worsening by socio-economic disadvantage over the last 3 decades in new South Wales, Australia - Hanna E. Tervonen; Sanchia Aranda; David Roder; Hui You; Richard Walton; Stephen Morrell; Deborah Baker; David C. Currow (BMC, 2017)
Abstract Background Public concerns are commonly expressed about widening health gaps. This cohort study examines variations and trends in cancer survival by socio-economic disadvantage, geographical remoteness and country of birth in an Australian population over a 30-year period. Methods Data for cases diagnosed in New South Wales (NSW) in 1980-2008 (n = 651,245) were extracted from the population-based NSW Cancer Registry. Competing risk regression models, using the Fine & Gray method, were used for comparative analyses to estimate sub-hazard ratios (SHR) with 95% confidence intervals (CI) among people diagnosed with cancer. Results Increased risk of cancer death was associated with living in the most socio-economically disadvantaged areas compared with the least disadvantaged areas (SHR 1.15, 95% CI 1.13-1.17), and in outer regional/remote areas compared with major cities (SHR 1.05, 95% CI 1.03-1.06). People born outside Australia had a similar or lower risk of cancer death than Australian-born (SHR 0.99, 95% CI 0.98-1.01 and SHR 0.91, 95% CI 0.90-0.92 for people born in other English and non-English speaking countries, respectively). An increasing comparative risk of cancer death was observed over time when comparing the most with the least socio-economically disadvantaged areas (SHR 1.07, 95% CI 1.04-1.10 for 1980-1989; SHR 1.14, 95% CI 1.12-1.17 for 1990-1999; and SHR 1.24, 95% CI 1.21-1.27 for 2000-2008; p < 0.001 for interaction between disadvantage quintile and year of diagnosis). Conclusions There is a widening gap in comparative risk of cancer death by level of socio-economic disadvantage that warrants a policy response and further examination of reasons behind these disparities.